Effects of Microalgae on Metabolic Syndrome - Kartthigeen Tamel Selvan; Jo Aan Goon; Suzana Makpol; Jen Kit Tan (MDPI AG, 2023)
Metabolic syndrome (MetS) is a cluster of metabolic disturbances, including abdominal obesity, hypertension, hypertriglyceridemia, reduced high-density lipoprotein cholesterol (HDL-C) and hyperglycemia. Adopting a healthier lifestyle and multiple drug-based therapies are current ways to manage MetS, but they have limited efficacy, albeit the prevalence of MetS is rising. Microalgae is a part of the human diet and has also been consumed as a health supplement to improve insulin sensitivity, inflammation, and several components of MetS. These therapeutic effects of microalgae are attributed to the bioactive compounds present in them that exhibit antioxidant, anti-inflammatory, anti-obesity, antihypertensive, hepatoprotective and immunomodulatory effects. Therefore, studies investigating the potential of microalgae in alleviating MetS are becoming more popular, but a review on this topic remains scarce. In this review, we discuss the effects of microalgae, specifically on MetS, by reviewing the evidence from scientific literature covering in vitro and in vivo studies. In addition, we also discuss the underlying mechanisms that modulate the effects of microalgae on MetS, and the limitations and future perspectives of developing microalgae as a health supplement for MetS. Microalgae supplementation is becoming a viable approach in alleviating metabolic disturbances and as a unique addition to the management of MetS.